Tourists' perceptions and assessments - Woodside, Arch G.; Kozak, M. 1968- (Advances in culture, tourism and hospitality research ;, 2014)
The volume examines unconscious and conscious cognitions occurring before, during and following virtual and actual leisure-related planned and unplanned travel. It includes a global review of the literature on tourists perceptions and assessments by Woodside and Metin.